Evaluation of the C-roundabout - an improved multi-lane roundabout design for cyclists. December 2012. - Asmus, D.; Jurisich, I.; Campbell, D.; Dunn, R. (My University, 2012)
The C-roundabout (cyclist roundabout) is a new multi-lane roundabout design (developed as part of a 2006 Land Transport NZ research project Improved multi-lane roundabout designs for cyclists) that aims to improve the safety of cyclists at multi-lane roundabouts and make multi-lane roundabouts more cyclist-friendly. A C-roundabout was installed at the Palomino Dr/Sturges Rd intersection in Auckland and was evaluated between 2008 and 2011 in terms of its safety, capacity, and the opinions of cyclists, pedestrians and car drivers. The C-roundabout successfully reduced vehicle speeds to 30km/hr, which is close to the speed of cyclists. This made the roundabout safer for cyclists, as well as for other road users. The installation of the C-roundabout at this uncongested site had little impact on capacity. It drew positive feedback from cyclists and pedestrians, but about half of the car drivers were not in favour of it. This could be expected as they may prefer a wider roundabout than the narrow C-roundabout. Another site (Margan Ave/Hutchinson Ave) was also reviewed and involved changing two approaches from wide single lanes to two narrow lanes, without altering the kerbs and with no reduction in design speed. The evaluation showed the capacity of a single-lane roundabout can be improved (almost doubled) at very low cost. However, the safety of the roundabout had decreased and a reduction in design speed was recommended to address this. (NZ TA)
Keywords: Individualverkehr; Fahrradverkehr; Verkehrssicherheit; Verkehrsplanung; Fahrradinfrastruktur; Radverkehrsanlage; Kreisverkehr; Radverkehrsführung; Evaluation